Have been working on this for the past 2 hours and still not getting any where. Any help will be much appreciated!
Consider the following argument
2) p v q
3) q → (r → s)
4) t → r
∴¬s → ¬t
Analyze the validity of the argument. If it is valid, show the proof with the inference rules & logical equivalence laws. If it is not valid, show a counterexample (which results in all premises being true but the condition being false).
I've tried using the basic inference rules (modus ponens/tollens, conjunctive simplification/addition, disjunctive addition/syllogism & hypotehtical syllogism) + the all the logical equivalence laws but am unable to derive an answer.